Molecular dynamics simulations of H2O with sites of Cu-I-FAU and Cu-II-FAU - Berthomieu, D.; Krishnamurty, S.; Heine, Thomas; Goursot, A. (Studies in surface science and catalysis, 2005)
A Born Oppenheimer molecular dynamic (BOMD) approach was chosen to study the interaction of water molecules with Cu-FAU models. We have compared the reactivity of Cu-I and Cu-II with the zeolite and compared the results to those calculated for Na. This Study shows a decrease of the coordination with time for Cu-I whereas there is not a significant change for Cu-II. BOMD shows also that, in the presence of water, Na+ may lead to easier cation exchange than for transition metal cations.
3rd Conference of the Federation-of-European-Zeolite-Association, Prague, CZECH REPUBLIC, AUG 23-29, 2005